PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Fitri Ramadhani; Delima Septiani (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study was to determine the mathematical communication skills of class VII students at Muhammadiyah Middle School in Pasir Penyu. This type of research is a Quasi Experiment with the design of Randomized Subject Posttest-Only Control Group Design. The data analysis technique in this test uses the t-test. Based on the calculation of the hypothesis test shows the significant value of the sample class is 0.003 0.05. Based on these results, H0 is rejected and Ha is accepted. So it can be concluded that the mathematical communication skills of students using the think talk write learning model is better than the mathematical communication skills of students using conventional learning models in class VII in the middle school Muhammadiyah Pasir Penyu.Keywords: Mathematical Communication, Think Talk Write